Understanding the impact of bullying and anti-bullying attitudes among indonesian adolescents: a correlational study - Ardani Sayyidatul Itsna; Suhendri Suhendri; Yunita Dwi Setyoningsih (Jurnal Konseling dan Pendidikan, 2026)
Bullying remains a significant concern in educational settings because of its potential negative consequences for students’ psychological, social, and academic development. Understanding the consequences of bullying may be associated with students’ attitudes toward rejecting and preventing bullying. This relationship can be considered from the Theory of Planned Behavior, in which attitude represents an important factor associated with behavioral intention and subsequent behavior. This study aimed to examine the relationship between understanding the impact of bullying and anti-bullying attitudes among Indonesian adolescents. A quantitative approach with a correlational design was employed. The participants consisted of 24 eighth-grade students from a population of 72 students, with eight students randomly selected from each of three classes in accordance with the school’s participation limit. Data were collected using researcher-developed instruments measuring understanding of the impact of bullying and anti-bullying attitudes. The final instruments consisted of 20 and 31 items, respectively, with Cronbach’s alpha coefficients of 0.904 and 0.965. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, linearity testing, and Pearson Product Moment correlation. The results showed a strong and statistically significant positive relationship between understanding the impact of bullying and anti-bullying attitudes (r = 0.726, p = 0.001). The correlation indicated a substantial shared variance between the two variables (r² = 0.527). These findings suggest that greater understanding of the consequences of bullying is associated with stronger anti-bullying attitudes. However, the correlational design does not establish a causal relationship between the variables. The findings provide empirical support for considering understanding of bullying impacts within preventive guidance and counseling services.